2022
DOI: 10.1093/ntr/ntac124
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Attentional Networks in Smoking Behavior Among Young Adults: Specific Contribution of Executive Control

Abstract: Introduction The exploration of cognitive impairments associated with tobacco use disorder has expanded during the last decades, centrally showing working memory and executive deficits among smokers. Despite their critical role in everyday life and in the smoking cessation process, attentional abilities have seldom been explored. Previous studies yielded discordant results, and the involvement of attentional deficits in smoking habits remains unclear. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…One study included in the quantitative synthesis reported data from an additional comparator group (‘Light Smokers’) ( 53 ). Therefore, to comply with the exclusion and inclusion criteria and the aim of this study, only the appropriate comparator groups were included in this meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…One study included in the quantitative synthesis reported data from an additional comparator group (‘Light Smokers’) ( 53 ). Therefore, to comply with the exclusion and inclusion criteria and the aim of this study, only the appropriate comparator groups were included in this meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…The studies included in the analysis originated from four countries, including the one from United States of America ( 30 ), five from China ( 5 , 18 , 21 , 43 , 54 ), two from Saudi Arabia ( 44 , 55 ), and one from Belgium ( 53 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations